Androgen-Dependent Sertoli Cell Tight Junction Remodeling Is Mediated by Multiple Tight Junction Components - Chakraborty, Papia (Endocrine Society, 2014)
Sertoli cell tight junctions (SCTJs) of the seminiferous epithelium create a specialized microenvironment in the testis to aid differentiation of spermatocytes and spermatids from spermatogonial stem cells. SCTJs must be chronically broken and rebuilt with high fidelity to allow the transmigration of preleptotene spermatocytes from the basal to adluminal epithelial compartment. Impairment of androgen signaling in Sertoli cells perturbs SCTJ remodeling. Claudin (CLDN) 3, a tight junction component under androgen regulation, localizes to newly forming SCTJs and is absent in Sertoli cell androgen receptor knockout (SCARKO) mice. We show here that Cldn3-null mice do not phenocopy SCARKO mice: Cldn3(−/−) mice are fertile, show uninterrupted spermatogenesis, and exhibit fully functional SCTJs based on imaging and small molecule tracer analyses, suggesting that other androgen-regulated genes must contribute to the SCARKO phenotype. To further investigate the SCTJ phenotype observed in SCARKO mutants, we generated a new SCARKO model and extensively analyzed the expression of other tight junction components. In addition to Cldn3, we identified altered expression of several other SCTJ molecules, including down-regulation of Cldn13 and a noncanonical tight junction protein 2 isoform (Tjp2iso3). Chromatin immunoprecipitation was used to demonstrate direct androgen receptor binding to regions of these target genes. Furthermore, we demonstrated that CLDN13 is a constituent of SCTJs and that TJP2iso3 colocalizes with tricellulin, a constituent of tricellular junctions, underscoring the importance of androgen signaling in the regulation of both bicellular and tricellular Sertoli cell tight junctions.